OA25 Is it time for patient-initiated methotrexate monitoring?. (23rd April 2022) - Wood, Natasha A. E; Farmer, Leila; Manhas, Roope; Lewis, Tom; Kyle, Stuart
Abstract: Background/Aims: Regular blood monitoring is recommended to ensure safety in patients on methotrexate (MTX). During the COVID pandemic, British Society of Rheumatology (BSR) sanctioned a reduction in monitoring for patients stable on MTX for 12 months. In accordance Devon CCG approved changing local Shared Care Guidelines (SCG), reducing the frequency to six monthly in stable MTX patients. Our aim was to assess whether monitoring frequency changed during the pandemic, and if so whether any patients came to harm. Methods: Patients stable on MTX monotherapy for at least a year to 31.3.2020 were identified via hospital pathology. 854 patients identified; the mean number of days between monitoring requests was calculated for the year to April 2020, and year to April 2021, respectively. A sub-analysis of 229 patients who had reduced from monthly to three monthly blood tests at similar time points was undertaken. Tests included: platelets (PLT), mean cell volume (MCV), neutrophils (NEUT), estimated glomerular filtration rate (eGFR), and alanine aminotransferase (ALT). Confidence intervals evaluated any differences in the results between monthly and three-monthly frequencies, in terms of overall distribution as well as at an individual patient level. Additionally, the numbers of 'catastrophic' test results, as defined by the Royal College of Pathologists, were calculated for the higher frequency and reduced frequency years. Results: Testing frequency in the year to April 2020 approximated to monthly, and three-monthly in the year to April 2021. Sub-analysis in 229 patients showed the overall distributions of PLT, MCV, NEUT, eGFR and ALT results were no more likely to be outside normal laboratory parameters when tested less frequently. Furthermore, individual patients were no more likely to have results outside normal laboratory parameters with less frequent testing. Overall, our analysis indicated that reduced monitoring did not lead to more abnormal results. Additionally, 'catastrophic' results were extremely uncommon, and did not increase with reduced testing. Routine MTX monitoring revealed no catastrophic results, these only occurred in patients being managed for co-existing morbidities. Conclusion: MTX monitoring reduced during the pandemic but not in adherence to updated SCG. We evidence that reducing frequency of routine blood monitoring did not increase abnormal results or cause harm in stable MTX patients. Significant blood abnormalities were rare and universally occurred only with co-existing morbidities. Across primary and secondary care workloads are increasing, resources are limited, and cost efficiencies needed. These findings support a review of the frequency of routine blood monitoring; is now the time to shift to patient-initiated testing in those stable on MTX monotherapy? Disclosure: N.A.E. Wood: None. L. Farmer: None. R. Manhas: None. T. Lewis: None. S. Kyle: None.